2019
DOI: 10.1002/jbt.22372
|View full text |Cite
|
Sign up to set email alerts
|

β‐Hydroxybutyrate exacerbates lipopolysaccharide/d‐galactosamine‐induced inflammatory response and hepatocyte apoptosis in mice

Abstract: β‐Hydroxybutyrate (BHB), one of ketone body, has been traditionally regarded as an alternative carrier of energy, but recent studies found that BHB plays versatile roles in inflammation. It has been previously reported that the level BHB declined in mice with lipopolysaccharide (LPS)/d‐galactosamine (d‐Gal)‐induced liver damage, but the pathological significance remains unclear. In the present study, the pathophysiological roles of BHB in LPS/d‐Gal‐induced hepatic damage has been investigated. The results indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Liver of LPS/D-Gal-treated mice often show apoptosis and necroptosis ( 35 ); we next investigated whether Pa or SA-Pa treatment could alleviate these cell deaths. TUNEL staining, which labels the exposed DNA termini due to apoptosis ( 36 ), showed that SA-Pa, but not Pa, treatment significantly reduced the injury-induced incidence of hepatocyte apoptosis ( Figure 6A and Supplementary Figure 3A ).…”
Section: Resultsmentioning
confidence: 99%
“…Liver of LPS/D-Gal-treated mice often show apoptosis and necroptosis ( 35 ); we next investigated whether Pa or SA-Pa treatment could alleviate these cell deaths. TUNEL staining, which labels the exposed DNA termini due to apoptosis ( 36 ), showed that SA-Pa, but not Pa, treatment significantly reduced the injury-induced incidence of hepatocyte apoptosis ( Figure 6A and Supplementary Figure 3A ).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the protective effects of β-HB may be mediated through metabolic signals by enhancing mitochondrial function for ATP generation. However, one report found that hepatocyte injury and apoptosis in mice with acute inflammation models induced by LPS and D-galactosamine were further exacerbated by β-HB administration [ 20 ]. The specific reasons may be related to the characteristics of different disease models, the mode of β-HB treatment and the therapeutic dose of β-HB, and further experimental investigation is required.…”
Section: Discussionmentioning
confidence: 99%
“…There may be a narrow and unique therapeutic window of BHB concentrations . BHB has been shown to enhance inflammation and apoptosis in the liver and enhance the cytotoxic effect of cisplatin in human hepatocellular carcinoma cells, , whereas it has displayed anti-inflammatory effects in other studies. , Moreover, it is reported that high BHB levels experienced increases in serum LDL cholesterol levels and the concentrations of HDL after medium-chain triglycerides (MCT) treatment, effective strategies to increase blood levels of the BHB, and intervention were significantly decreased. , Both high LDL levels and low HDL levels are considered risk factors for ischemic stroke. Thus, we suppose that the possible toxic effects and decreased effectiveness of high doses of BHB may be due to increased effects of BHB on cholesterol metabolism and the inflammatory response.…”
Section: Discussionmentioning
confidence: 99%